2018
DOI: 10.1136/bmjsem-2018-000403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate-intensity exercise bouts lasting <10 minutes on body composition in sedentary Kenyan adults aged ≥50 years

Abstract: BackgroundSedentary lifestyles and related morbidities are rising among adults despite existing exercise recommendations. Appealing exercise regimes yielding similar/better body composition should be sought.ObjectiveWe investigated the effect of moderate-intensity exercise bouts of <10 min on body composition in previously sedentary adults.MethodsThis unblinded study enrolled 53 healthy sedentary volunteers aged ≥50 years, randomised into one of two gender-balanced exercise interventions: (1) male and (2) fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Opinions differ on the benefits of short exercise bouts,11–17 and a different approach in regime, population or setting that addresses the lack of PA/exercise could be useful. In a previous study involving the same population as in this study, we found that shorter exercise sessions are beneficial in improving cardiometabolic markers and body composition 18 19. However, the few studies that have tested the effect of supervised exercise bouts on cardiac performance among the elderly have shown conflicting results 20–22.…”
Section: Introductionmentioning
confidence: 49%
“…Opinions differ on the benefits of short exercise bouts,11–17 and a different approach in regime, population or setting that addresses the lack of PA/exercise could be useful. In a previous study involving the same population as in this study, we found that shorter exercise sessions are beneficial in improving cardiometabolic markers and body composition 18 19. However, the few studies that have tested the effect of supervised exercise bouts on cardiac performance among the elderly have shown conflicting results 20–22.…”
Section: Introductionmentioning
confidence: 49%
“…The mechanisms in body composition and cardiovascular measurements change following an F-7.5m-MIE is somewhat same as that in the longer regime. Previous studies from our set up and elsewhere have shown that shorter prescribed bouts could actually yield better outcomes on body composition and cardiovascular measures [30,31,39,47], which differences, although apparent but minimal in the current work, could not be pursued further for direction because our design could not support testing for superiority.…”
Section: Plos Global Public Healthmentioning
confidence: 72%
“…It is likely that the 12 weeks follow-up period could not allow clear and appreciable changes as weight reduction which affects BMI has been shown to be slower than other anthropometric measurements such as waist circumference change that affects WHR and WHtR, explaining the differences observed in these measures [42]. We previously observed positive changes in body composition from the same setting on healthy-sedentary individuals by use of comparable exercise regimes [31]. Elsewhere, similar follow-up periods for accumulated shorter bouts of exercise have yielded favourable body compositions [43,44], although they were not specific for individuals with prehypertension.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 2 more Smart Citations